2012 Florida Constitutional Amendment 9: Homestead Property Tax Exemption for Surviving Spouse of Military Veteran or First Responder - Rodney L. Clouser (EDIS)
In addition to 2012 being a presidential election year, Florida voters also will be asked to vote on a number of proposed amendments to their state constitution. Many voters remain either unaware or less informed regarding the effects and impacts of the proposed constitutional amendments. This document is one of a series of 6 fact sheets that was written by Rodney L. Clouser and published by the UF Department of Food and Resource Economics, July 2012.